Sposoby uczestniczenia prawników w kulturze - Zirk-Sadowski, Marek (Wydział Prawa i Administracji UAM, 1994)
The author looks at the legal system as a sub-system in the system of cultural norms. In that context the participation of lawyers in culture, as it arises from their specific function in the society, is discussed. The participation of lawyers in culture has been described as a reflexive participation in a certain communication community. Different forms of such participation in different societies have been considered with a view of finding why there is a common and widespread tendency to treat the participation of lawyers in culture only instrumentally. Finally the author postulates a form of a dialogue culture characterised by a critical/innovative approach.
Participation of lawyers in the culture